Penampilan Burung Puyuh (Coturnix-coturnix japonica) yang diberi Tepung Jeroan Ikan Cakalang sebagai Pengganti Tepung Ikan - Taufik Dauhi; Srisukmawati Zainudin; Syukri I Gubali (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The research objective was to evaluate the provision of skipjack tuna offal flour as a substitute for fish meal in quail rations. The research was conducted in August - October 2020 in Boidu Village, North Bulango District, Bone Bolango Regency, Gorontalo Province. The research design used was a completely randomized design (CRD). The use of skipjack offal flour in the ration had no significant effect (P 0.05) on ration consumption, ration conversion and body weight gain between treatment and control. The use of skipjack fish offal flour up to a content of 12% as a substitute for fish meal can be used in super native chicken rations.